Plausible ergogenic effects of vitamin D on athletic performance and recovery - Dahlquist, D.; Dieter, B.; Koehle, M. (Journal of the International Society of Sports Nutrition, 2015)
The purpose of this review is to examine vitamin D in the context of sport nutrition and its potential role in optimizing athletic performance. Vitamin D receptors (VDR) and vitamin D response elements (VDREs) are located in almost every tissue within the human body including skeletal muscle. The hormonally-active form of vitamin D, 1,25-dihydroxyvitamin D, has been shown to play critical roles in the human body and regulates over 900 gene variants. Based on the literature presented, it is plausible that vitamin D levels above the normal reference range (up to 100 nmol/L) might increase skeletal muscle function, decrease recovery time from training, increase both force and power production, and increase testosterone production, each of which could potentiate athletic performance. Therefore, maintaining higher levels of vitamin D could prove beneficial for athletic performance. Despite this situation, large portions of athletic populations are vitamin D deficient. Currently, the research is inconclusive with regards to the optimal intake of vitamin D, the specific forms of vitamin D one should ingest, and the distinct nutrient-nutrient interactions of vitamin D with vitamin K that affect arterial calcification and hypervitaminosis. Furthermore, it is possible that dosages exceeding the recommendations for vitamin D (i.e. dosages up to 4000-5000 IU/day), in combination with 50 to 1000 mcg/day of vitamin K 1 and K 2 could aid athletic performance. This review will investigate these topics, and specifically their relevance to athletic performance.